Рубежи славы - Мощанский Илья Борисович (Забытые страницы Второй мировой, 2010)
Экземпляры: (20220422) / Инвентарный номер: 35081 / Цена: 134.97 / Сис.шифр: 63.3(2)62 / Авт.знак: М 87 / ГРНТИ: 03 / ББК: 63.3(2)62